2022
DOI: 10.1080/14786419.2022.2140150
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites isolated from Penicillium christenseniae SD.84 and their antimicrobial resistance effects

Abstract: A pair of new quinolone alkaloid enantiomers, (Ra)-(-)-viridicatol (1) and (Sa)-(+)-viridicatol (4), along with seven known compounds 2, 3, and 5-9 were isolated from Penicillium christenseniae SD.84. The structure of 1and 4 ware determined by NMR and HRESIMS data. Compound 1 and 4 were determined to be a pair of enantiomers by theoretical calculation through CD and ECD. The MIC values of compound 4 against Staphylococcus aureus and methicillin-resistant Staphylococcus aureus were 12.4 μM and 24.7 μM, compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…In another study, compounds isolated from A. burnettii had antimicrobial activity against Bacillus subtilis, Staphylococcus aureus, Candida albicans and Saccharomyces cerevisiae in the bioassay screening (Gilchrist et al, 2020) indicating that extracts from fungal endophytes in the genus Aspergillus have antimicrobial properties. Antifungal activity of P. christenseniae is in line with the findings of Wang et al (2022) indicated that secondary metabolites isolated from this fungus had antimicrobial activity against S. aureus and methicillinresistant S. aureus.…”
Section: Isolation and Antifungal Activity Of A Abyssinicus Fungal En...supporting
confidence: 84%
See 2 more Smart Citations
“…In another study, compounds isolated from A. burnettii had antimicrobial activity against Bacillus subtilis, Staphylococcus aureus, Candida albicans and Saccharomyces cerevisiae in the bioassay screening (Gilchrist et al, 2020) indicating that extracts from fungal endophytes in the genus Aspergillus have antimicrobial properties. Antifungal activity of P. christenseniae is in line with the findings of Wang et al (2022) indicated that secondary metabolites isolated from this fungus had antimicrobial activity against S. aureus and methicillinresistant S. aureus.…”
Section: Isolation and Antifungal Activity Of A Abyssinicus Fungal En...supporting
confidence: 84%
“…contains active natural products and this secondary metabolites are involved in inhibitory activities against microbes (Kozlovskii et al, 2013). Presence of alkaloids in P. christenseniae crude extracts is in line with the findings of Wang et al (2022) whereby, two new quinolone alkaloid enantiomers, (Ra)-(-)-viridicatol (1) and (Sa)-(+)-viridicatol (4) and seven other known compounds were isolated from P. christenseniae SD.84. The presence of steroids in P. christenseniae ethyl acetate crude extract could have contributed to the inhibition of 10.3±0.6 mm, with the difference in inhibition being probably a result of synergy of the chemical constituents present in each extract.…”
Section: Screening Of Chemical Constituents Of the Fungal Endophyte E...supporting
confidence: 71%
See 1 more Smart Citation